A Semiotic Analysis of No-Smoking Warning Labels on Cigarette Packaging - Firsa, Muh Firsa Wirawan; Evi Irawanti BR Saragih; Ayu Triria Puspita Devi; Mutmainnah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study attempts to analyze semiotic elements and messages intended for readers, focusing specifically on the types of signs according to Charles Sanders Peirce. Data was obtained from five cigarette package of no smoking warning labels, which were analyzed using Charles Sanders Peirce’s theory of semiotics. This study uses a qualitative descriptive method with the aim of descriptively explaining. The primary data for this study were obtained from Indonesian cigarette packages currently on the market, all of which are actively distributed and available to consumers, ensuring that the data reflects current industry practices and market conditions. The brands collected in this particular study include Glory, Nation Bold, Filasta, Dio, and Sampoerna, representing a range of commonly available products. Based on this study, it was revealed that cigarette warning labels are strategically designed to reduce global smoking prevalence by presenting visual depictions of smoking-related illnesses alongside explicit health warnings. These measures aim to increase public awareness and influence behavior, thereby reducing both the frequency and intensity of smoking.